Comment analyser ce que font les enseignants dans la préparation de leurs cours ? Ébauche d'un cadre conceptuel - Jean-Philippe Maitre; Michaël Huchette; Éric Bruillard (Nantes Université, 2018)
Preparing their lessons, teachers produce material and media from resources that are their own but also found on the Internet, or by asking colleagues, etc. This ordinary activity is in fact complex and poorly documented. How teachers start the preparation of their lessons? With what materials? How do they find and/or build what they use in class? How this material is (or not) recycled years after years? This article presents few theoretical guidelines to analyse these questions. Its content fit in the ReVEA project (supported by the ANR) that is briefly described. Our arguments are supported both by the literature - rare on the subject - and data, gathered through interviews with French technology secondary school teachers and high school technological and engineer sciences teachers. Our conclusion raises the question of the systemic aspect of the organization of this part of the teachers' work, opening new perspectives of research.